Comparison of diclofenac suppository administration time on post-operative pain in transvaginal oocyte retrieval under general anesthesia: a double-blind randomized clinical trial - Pouran Hajian; Niloofar Molai; Mahshid Nikooseresht; Abbas Moradi (Mashhad University of Medical Sciences, 2021)
Introduction: Considering the sensitive morale of patients undergoing in vitro fertilization, there is controversy regarding the severity of pain experienced after oocyte retrieval, the appropriate analgesic drug and the time of its administration in these patients. This study was performed with aim to compare the time of administration of diclofenac suppository on post-operative pain after transvaginal oocyte retreival under general anesthesia. Methods: This clinical trial study was performed on 70 female candidates for oocyte retrieval at Infertility Center of Fatemieh Research Hospital in 2018. The subjects were randomly divided into two groups of A and B (n=35 in each group). Group B received 100 mg diclofenac suppository 15 minutes before oocyte extraction from follicle and group A  immediately after oocyte extraction from ovarian follicles. Pain severity was assessed using visual analogue scale of pain (VAS) after recovery at 15, 30, 60, 90, 120 minutes. Data were analyzed by SPSS software (version 16). T-test was used to compare the mean of data with normal distribution; otherwise nonparametric Mann-Whitney test was used.  Chi-square test (Fisher Exact test) was used to compare the qualitative data. P<0.05 was considered statistically significant. Results: Both groups had no significant difference in terms of mean age, education level, number of retrieved oocytes, duration of anesthesia, anesthetic drug and hemodynamic status (P > 0.05). 25 patients in group B (71.4%) and 32 in group A (91.4%) had abdominal or vaginal pain after anesthesia (P = 0.03). The mean of total pain intensity in group B was less than group A in the first 120 minutes after anesthesia; there were significant differences at 15 and 90 minutes after anesthesia (P=0.032, P=0.017, respectively). Nausea and vomiting were observed in 4 patients (11.4%) of group B and 3 (8.6%) of group A (P= 0.690). None of the patients had post-operative bleeding. Conclusion: Administration of diclofenac sodium suppository prior to oocyte extraction from follicle was more effective in patients' analgesia than administration after oocyte extraction from follicle.